Abnormalities in fibrinolysis at the time of admission are associated with deep vein thrombosis, mortality, and disability in a pediatric trauma population. Issue 1 (January 2017) - Leeper, Christine M.; Neal, Matthew D.; McKenna, Christine; Sperry, Jason L.; Gaines, Barbara A.
Abstract : BACKGROUND: Abnormalities in fibrinolysis are common and associated with increased mortality in injured adults. While hyperfibrinolysis (HF) and fibrinolysis shutdown (SD) are potential prognostic indicators and treatment targets in adults, these derangements are not well described in a pediatric trauma cohort. METHODS: This was a prospective analysis of highest level trauma activations in subjects aged 0 to 18 years presenting to our academic center between June 1, 2015, and July 31, 2016, with admission rapid thrombelastograph. Shutdown was defined as LY30 (lysis 30 minutes after the maximum amplitude has been reached) of 0.8% or less and HF defined as LY30 of 3.0% or greater. Variables of interest included demographics, admission vital signs and laboratory values, injuries, incidence of venous thromboembolism under our screening protocol, death, and functional disability (discharge to facility or dependence in functional independence measure category). Youden index determined optimal definition of SD, then Wilcoxon rank-sum, Kruskal-Wallis, and Fisher exact tests were performed. RESULTS: One hundred thirty-three patients are included with median age of 10 years (interquartile range [IQR], 5–13 years); male sex, 5.4%; median Injury Severity Score, 17 (IQR, 10–26); blunt mechanism, 68.4%. Youden analysis defined SD as LY30 of 0.8 or less. In total, 38.3% (n = 51) had SD on admission; 19.6% (n = 26) had HF, and 42.1% (n = 56) were normal. Mortality rate was 9.0% (n = 12), and deep vein thrombosis incidence was 10.7% (n = 13/121 surviving). Shutdown and HF were both associated with mortality ( p = 0.014 and p = 0.021) and blood transfusion ( p = 0.001 and p < 0.001); SD was also associated with disability ( p < 0.001) and deep vein thrombosis ( p = 0.002). Blunt mechanism was associated with SD, and penetrating mechanism was associated with HF ( p = 0.011). Both SD ( p = 0.001) and HF ( p = 0.036) were associated with elevated international normalized ratio. LY30 did not differ significantly across age groups. CONCLUSIONS: Children demonstrate high rates of inhibition (SD) and overactivation (HF) of fibrinolysis after injury. Shutdown and HF are both associated with poor outcomes. Shutdown is a particularly poor prognostic indicator, accounting for the greatest percentage of death, disability, and patients requiring transfusion, as well as later development of hypercoagulable state. The addition of thrombelastograph to pediatric trauma care protocols should be considered as it contributes important prognostic and clinical information. LEVEL OF EVIDENCE: Prognostic and epidemiologic study, level III.